Factors Causing Failure of the REDD+ Program Implementation in Central Kalimantan - Lestari, Nanik (Jurnal Manajemen Hutan Tropika, 2019)
Deforestation becomes a crucial issue in the context of climate change. Deforestation in Southeast Asia is more serious than in Amazonia and Central Africa due to forest clearing done for economic activities such as agriculture and timber production. Among the ASEAN countries, Indonesia contributes to the biggest number. In order to solve this issue, Indonesia cooperates with the Government of Norway to implement the Reducing Emission from Degradation and Deforestation Plus (REDD+) program. The program is implemented in several regions in Indonesia as pilot projects. One of them is in Central Kalimantan. Although many resources are spent to support the success of the program in Central Kalimantan, it seems that the program does not successfully solve the problem for Central Kalimantan Province suffers high degradation and deforestation. Therefore, this study aims to investigate the causes of failure in implementing the REDD+ program in Central Kalimantan by using the bottom-up implementation model. This study applied a qualitative method. The informants in this study were government and non-government agents involved in the REDD+ implementation in Central Kalimantan, such as Lembaga Dayak Panarung, Aliansi Masyarakat Adat Nusantara of Central Kalimantan, and Wahana Lingkungan Hidup Indonesia. Data were collected using interview and observation. Collected data from interview and observation were supported by secondary data. This study found that there are two major problems causing the failure of REDD+ implementation. The first problem is different perceptions between the communities. They thought that the REDD+ program was a project that only benefited to certain groups. Furthermore, the practice of bad forestry governance triggers bad implementation.